A Compact Size 4–19.1 GHz Heart Shape UWB Antenna with Triangular Patches - Gokmen Isik; Serkan Topaloglu (International Journal of Antennas and Propagation)
An ultrawideband antenna is designed, simulated, and realized. To overcome the narrow bandwidth characteristics of basic patch antennas, the structure of the radiation pattern is optimized by the aid of elliptical and rectangular patches. Also triangular patches are applied to the antenna edge in order to enhance the VSWR and gain properties. A typical VSWR of 1.5 (less than 2 in the whole frequency range) and a typical gain of 2 dBi (mainly above 1 dBi in the whole frequency range) are observed. The simulations present that the designed antenna has a bandwidth ratio of ~5 : 1 within the frequency range of 4–19.1 GHz with compact dimensions of 25 × 26 mm2. It is fabricated on a 0.5 mm thick, RO3035 substrate. The input impedance, gain, and radiation characteristics of the antenna are also presented. With these properties, it is verified that, with its novel shape, the proposed antenna can be used for various UWB applications.